P‐47: 10K Ultra‐High‐Definition Display System. Issue 1 (May 2016) - Ran, Duan; Michelini, Pablo Navarrete
Abstract : Our 82' 10K display panel shown in SID 2015 only supported a 10K input signal. We show our upgraded 10K system that now includes several processing and enhancement modules. By integrating SOC and FPGA technologies, we are now able to provide a powerful multi‐input and unique UHD system.